The Role of the Function of the Binmas Unit in Reducing the Crime of Abuse through Focus Group Discussion at Tasikmalaya Police - R, Bramastha Hanif (Indonesian Journal of Police Studies, 2024)
The focus of this thesis research is the influence of the implementation of Focus Group Discussion in reducing the crime of sexual abuse in the Tasikmalaya Regional Police Station. The focus of this thesis research was important because the implementation of the Focus Group Discussion conducted by the Tasikmalaya Regional Police Binmas Unit is expected to reduce the cases of sexual abuse in the Tasikmalaya district. In this thesis research has 2 problems that will be researched in this thesis research,those are: 1. What are the factors that become the cause crime of sexual abuse happen in the Tasikmalaya Regional Police? 2. How is the implementation of Focus Group Discussion conducted by the Binmas Unit in reducing the crime? 3. How the next action that will be done by the Binmas to reduce the crime of sexual abuse through a Focus Group Discussion at the Tasikmalaya Regional Police Station? The technique of analyzing these 2 problems, the author uses descriptive analysis method with a qualitative approach. The use of a conceptual framework in the form of theories and concepts was sharped the analysis by the author to analyze the problem formulation that discuss formulation of the problem that has been determined. Theories and concepts used by the author are debating theory, Infinite management theory, Theory of basic concepts of management.In using the concept, the writer uses the concept of community development unit, the concept of Focus Group Discussion. This study found several findings results 1. There is an increase in cases of sexual abuse in the Tasikmalaya Regional Police, especially in 2019 2. There isn’t undistribution happened of Focus Group Discussion material about the crime of sexual abuse to the public especially the material about sexual abuse was only done once in October 2019 3. The less community understanding of the Child Protection Act, this is evidenced because the majority of incidents of sexual abuse occur within the internal scope of the family or it was called “inses”. 4. The lack of personnel of the Binmas Unit can hamper the performance of the Binmas Unit. Therefore, in the research on the Tasikmalaya Regional Police to further intensify the implementation of Focus Group Discussions with awareness materials about molestation and discussing the Child Protection Act, and ask personnel for the Binmas Unit to improve the performance of the Tasikmalaya Regional Police Unit beside that as well as adding and maintaining, increasing the capability of Tasikmalaya Regional Police Binmas Unit personnel.